Studies on the Comparative Effect of Organic and Synthetic Feed on the Growth and Serum Metabolites of Broiler Chicks - Sadia Shahid, Muhammad Tahir, Amara Akhtar, Muhammad Usman, Sajid Abbas Khan, Hafeez Ullah, Laraib Maryum, Sajid Raza Khan, Qamar Shahzad Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Modern broiler production efficiency is built on the improved feed for high growth and egg output. Growth performance of broilers greatly influenced by the feed contents. Objective: The objective of this study was to analyze the impact of organic and synthetic feed on the growth, feed utilization and serum metabolites of broilers chicken. Material and Methods: This experiment was conducted for 28 days on broiler chickens. Broilers were divided into five treatments such as T0, T1, T2, T3 and T4. Control group T0 received basal diet. T1 and T2 received organic feed. T3 and T4 received synthetic feed. Results: All the feed were given at the levels of 3% and 6%. Feed were given orally in the form of pellets. Conclusion: Results showed that value of WG, absolute weight gain and SGR were increased significantly (p<0.05) in combine treatment T2 (6% organic feed) with respect to T0 (control group). Feed intake and FCR was significantly (p<0.05) in treatment T2. Serum metabolites i.e. cholesterol, triglycerides, glucose and total protein were significantly analyzed (p<0.05).The result of present study explained that T2 having organic feed showed better growth performance of broiler chickens. Keywords: broilers chicken, feed requirement, weight gain, FCR, serum metabolites,